2017
DOI: 10.22158/jepf.v3n3p330
|View full text |Cite
|
Sign up to set email alerts
|

The Lebanese Perception of the Impact of Small & Medium Enterprises (SMEs) on the National Economy

Abstract: Over the years, Small and Medium-Sized Enterprises (SMEs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Rotar, Pamić, and Bojnec (2019) also found that there is a significant correlation between MSEs and labor absorption in the service industry. Gebremariam and Gebremedhin (2004); Hamdar, Najjar, and Karameh (2017); Manzoor et al (2019) found that the growth of SMEs contributes to the reduction of poverty through the economic growth and unemployment reduction. Darma et al (2020) investigated brown sugar as one of MSE products in Indonesia and found that the use of appropriate technology could absorb more labor and increase the income of rural communities.…”
Section: Literature Surveymentioning
confidence: 99%
“…Rotar, Pamić, and Bojnec (2019) also found that there is a significant correlation between MSEs and labor absorption in the service industry. Gebremariam and Gebremedhin (2004); Hamdar, Najjar, and Karameh (2017); Manzoor et al (2019) found that the growth of SMEs contributes to the reduction of poverty through the economic growth and unemployment reduction. Darma et al (2020) investigated brown sugar as one of MSE products in Indonesia and found that the use of appropriate technology could absorb more labor and increase the income of rural communities.…”
Section: Literature Surveymentioning
confidence: 99%
“…Small and medium enterprise (SME) is widely considered as a powerhouse of an economy (Khazanchi, 2005; Halim et al , 2017). SME significantly improves the income distribution scenario, generates employment and reduces poverty (Hamdar, 2017; Nosratabadi, 2020). For example, approximately 90% of formal and informal businesses are SMEs in developing countries.…”
Section: Introductionmentioning
confidence: 99%